Evidence-Based Medicine Appraisal Companions - Rani Gereige (Association of American Medical Colleges, 2006)
Abstract Evidence-based medicine (EBM) skills can be used by health professionals throughout their careers. EBM allows the clinician to critically appraise the published literature when looking for answers to patient-based clinical questions. If learned well during medical school, EBM skills can be valuable tools for lifelong education during and beyond residency. EBM is used to make clinical decisions based on available evidence, taking into account patient preferences, values, and culture. The EBM appraisal companions in this resource are worksheets designed to guide the novice learner through the critical appraisal process via a stepwise approach allowing practice and interpretation of various statistical formulae and calculations. The worksheets direct the user to critical areas for appraising the validity of published literature in relation to a clinical scenario. They can be used in the context of an EBM course to complement didactic work by allowing students to apply their learned skills in the context of a particular published article. They could also be used for faculty development in EBM skills, as part of residency training curriculum, or in the context of small-group discussions, journal clubs, or even morning reports. The major topics addressed include the appraisal of articles on therapy, diagnostic tests, harm/association, and prognosis. The companions are structured with drop-down menus, check boxes, and comment/free-text sections. Background knowledge in the basic EBM principles is required.